The moral duty to help others from a Кantian perspective. Part ІІ. Issues in the practical implementation - Maslikova, Iryna (Ukrainian Cultural Studies, 2025)
Background. The article highlights the importance of Kantian ethics of duty, which defines the nature and essence of the moral duty to help others. The theoretical impossibility of establishing limits for the fulfilment of the moral duty to help others and the complexity of an imperfect world make the practical implementation of helping others problematic. The goal of the article is to identify the nature, strength, and effectiveness of the moral duty to help others from the Kantian perspective of deontological ethics. The task of the second part is to identify practical problems in the implementation of the moral duty to help others. Methods. The article uses methods of analysis and synthesis in determining the prospects for modifying deontological ethics. Results. The main problems of realising the duty to help others are related to issues of justice, which arise as a result of limited resources, the physical ability of agents to help, and possible manipulation by benefactors. Kant’s "formula of humanity" acts as a safeguard against injustice, which can manifest itself in the use of those in need as a means of realising the "goodwill" of the benefactor. In order to resist various temptations that arise against the backdrop of limited resources, the special virtues of moral agents become important in strengthening their ability to fulfil their moral duty to help others. To fulfil the moral duty to help others at the level of individual action, it is important to personally know those who need help. For the implementation of institutional assistance, the principles of impartiality and the value of the human personality are decisive. The full implementation of the duty to help depends on the circumstances – to a greater extent, the requirements of humanitarian assistance as a "narrow" duty to save lives must be implemented, while the requirements of charitable assistance are "broader" and depend on the benefactor’s ability to realise them. Conclusions. The prospects for strengthening moral motivation to provide assistance are related to an understanding of the benefactor’s ability to provide assistance, taking into account both their needs and the needs of those in difficult situations. Strengthening moral motivation is possible through the development of moral feelings, in particular empathy, and the cultivation of "exceptional" virtues, in particular courage and generosity. This opens up opportunities for modifications to deontological ethics by broadening the understanding of human nature as both rational and sentimental beings.